Evaluation of parathyroid function in adult male patients with transfusion dependent thalassemia - Urmi, SFH; Begum, Shelina; Munira, Fatema Tuz (Journal of Bangladesh Society of Physiologist, 2020)
Background: In transfusion dependent thalassemic (TDT) patients regular blood transfusion leads to iron overload. This increased iron is deposited in the tissue of various system and causes organ damage. Endocrine dysfunction is very common due to iron deposition into the endocrine glands including parathyroid dysfunction. Objective: To measure plasma intact parathyroid hormone(iPTH), serum total calcium and inorganic phosphate levels in adult male patients with TDT. Methods:This cross sectional study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University, Dhaka from March 2018 to February 2019. Total 35 TDT male patients aged 18 to 40 year and 35 age matched apparently healthy male subjects were enrolled for this study as control. The TDT patients were selected from the outpatient department of Hematology and Transfusion Medicine. For assessment of parathyroid function serum albumin, plasma iPTH, serum total calcium and inorganic phosphate levels were estimated by colorimetric method using automated analyzer. For statistical analysis, independent sample t test was done. Results: In this study, plasma iPTH and serum corrected calcium levels were significantly (p < 0.001) lower in patients with TDT than those of healthy control. Again, Serum inorganic phosphate and ALP levels were significantly (p < 0.001) higher in patients with TDT than those of healthy control. Moreover, 2.86% of TDT patients had low iPTH. Conclusion: From this study, it can be concluded that reduced parathyroid function was associated with TDT. J Bangladesh Soc Physiol. 2019, December; 14(2): 77-81